Role of assessment, Selecting the right methods of assessment for your course, constructive alignment and role of feedback - Alfredo Soeiro (2020)
Assessment is considered as the most important role in steering the learning process; however we cannot confined to one particular methodology as the best assessment method for a course. An assessment plan helps in selecting the right testing method and decides on the relative weight of each assessment for the final result of a course. This also helps to ensure that the assessment addresses the intended learning outcomes. In addition, it provides a good overview of the test arrangement for a course that will be published in the course manual. This makes an assessment plan a helpful tool for examiners and an important instrument for quality assurance which makes the first module of the course. An assessment matrix is designed to ensure that all the selected learning objectives are covered in the assessment which helps to make certain that the assessment will be both valid and reliable which provides the insights for the second module. This is done by using different methods to set the cut-off score by using rubrics. In the third module, the participants will be put forward to apply quality criteria for the construction of assessments and assessment items to improve the quality of assessments and education which have huge impact on the future education and careers of students. In the fourth and final module of the course the participants will find answers for the following questions 1) on which aspects did students perform well, and where did they fail? 2) If good students fail on certain questions, what does this say about the question or about teaching? 3) We may need to decide on how to fix certain errors or unexpected situations and think about how this affects students' grades 4) what are the things to consider when performing an exam or item analysis? 5) What do you look for? 6) How do you draw conclusions and make plans for future improvements? During the course, the participants will be guided through the different phases of preparing, creating and evaluating the assessments through instructional videos, interviews, animations and checklists. In addition to these, there will be course activities, such as assessments, and discussion prompts.